93.4k views
3 votes
Simplify the expression. (1-cot(x))^2/cot(x)=

2 Answers

2 votes

Answer:

tan(x) + cot(x) - 2

Explanation:

User Joejoeson
by
5.3k points
6 votes

Answer:

tan(x) + cot(x) - 2

Explanation:

We can see the answer to the question in the images provided below.

Please, see attached picture.

(1-cot(x))^2 = 1 - 2 cot(x) + cot^2(x)

If we divide by cot(x)

We get

tan(x) + cot(x) - 2

Simplify the expression. (1-cot(x))^2/cot(x)=-example-1
Simplify the expression. (1-cot(x))^2/cot(x)=-example-2
User Drew Nutter
by
6.0k points